The Effect of the Self-Questioning Strategy on the Achievement of Fourth-Grade Female Students in the Subject of the History of Arab-Islamic Civilization - Manal Younis Majeed (Zanco Journal of Human Sciences, 2025)
The current research aims to identify the innovations of the self-questioning strategy in the achievement of female students of the fourth literary grade in the subject of the history of Arab-Islamic civilization. The research was limited to female students of Jerusalem Preparatory School for the fourth literary grade, the preparatory stage in Diyala Province, Baqubah District, the Sabahiya Academic Center for Classical Dance 2023/2024, as the number of female research students reached Subjective (46) students were divided into two equal groups, choosing the experimental group according to the strategic questions The control group was studied and the normality was explained. The research asked to obtain a research tool consisting of (30) and it was proven true and reliable. The researcher examined the test on an exploratory view of (30) female students and after applying the research tool beforehand and afterward on two experimental and control lectures, examining the data and examining the statistical results. There is a statistically significant difference between the average of the experimental group that used the self-questioning strategy. Also, the results show that there is a statistically significant difference between the average of the experimental group that learned and knew the normal approach in entrance achievement.